1990
DOI: 10.3109/10715769009109664
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking Induces Formation of 8-Hydroxydeoxyguanosine, One of the Oxidative Dna Damages in Human Peripheral Leukocytes

Abstract: Active oxygen species (AOS) such as O2- and H2O2 have been shown to be generated from both gas and tar phases of cigarette smoke and it has been suggested that they are involved in carcinogenesis due to cigarette smoking. Therefore, we investigated the effect of cigarette smoking on oxidative DNA damages in human peripheral blood cells using 8-hydroxydeoxy-guanosine (8-OH-dG) as a marker. From ten healthy male volunteers aged 20-22 years, 5 ml of blood was taken before and 10 minutes after smoking 2 cigarettes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(77 citation statements)
references
References 14 publications
3
73
0
1
Order By: Relevance
“…Fume particles and noxious gases such as nicotine and carbon monoxide may influence the circulatory system by inducing profound vasospasm, platelet aggregation, or leading to oxidative damage to lipids, proteins, and cellular DNA. [2][3][4][5][6][7][8] Epidemiological data link cigarette smoking as a risk factor for many ophthalmological disorders including strabismus in offspring of pregnant smokers, anterior ischaemic optic neuropathy, age related macular degeneration, cataract, thyroid ophthalmopathy, primary open angle glaucoma, diabetic retinopathy, uveal melanoma, conjunctival intraepithelial neoplasia, ocular sarcoidosis, and development of dry eyes. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] The Beaver Dam Study related current active smoking and past history of smoking to a higher prevalence of dry eye disease.…”
Section: Introductionmentioning
confidence: 99%
“…Fume particles and noxious gases such as nicotine and carbon monoxide may influence the circulatory system by inducing profound vasospasm, platelet aggregation, or leading to oxidative damage to lipids, proteins, and cellular DNA. [2][3][4][5][6][7][8] Epidemiological data link cigarette smoking as a risk factor for many ophthalmological disorders including strabismus in offspring of pregnant smokers, anterior ischaemic optic neuropathy, age related macular degeneration, cataract, thyroid ophthalmopathy, primary open angle glaucoma, diabetic retinopathy, uveal melanoma, conjunctival intraepithelial neoplasia, ocular sarcoidosis, and development of dry eyes. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] The Beaver Dam Study related current active smoking and past history of smoking to a higher prevalence of dry eye disease.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors 30 have also investigated the effect of smoking on oxidative damage to DNA in peripheral blood cells. These authors used 8-hydroxydeoxyguanosine (8-OH-dG) as a marker.…”
Section: Discussionmentioning
confidence: 99%
“…The observation of nearly seven-times more differences in 8-OHdG levels obtained from leukocytes DNA of nonsmokers leads to idea that genetic factors and lifestyle may have effect on the increase of 8-OHdG level. According to some studies, age factor, smoking, and working hours in jobs carrying threats of cancer risk goes parallel with the increase of urinary 8-OHdG level (26) . In our study, we have found a positive (r = 0.42, p <0.05) difference between 8-OHdG/creatinine ratio and smoke in PCOS patients but we have not found any significant difference between PCOS patients with smokers and non-smokers in terms of 8-OHdG/creatinine ratio.…”
Section: Discussionmentioning
confidence: 99%